PELAYANAN PEMBIAYAAN KREDIT MOTOR HONDA DI LEASING FEDERAL INTERNATIONAL FINANCE (FIF) - Mardianti, Ratna Putri; Khadijah, Khadijah; Fadilah, Andi Hidayatul; Richmayati, Maya (ASOSIASI IDEBAHASA KEPRI, 2026)
This study discusses the financing services for new motorcycle credit provided by PT Federal International Finance (FIF), one of the largest leasing companies in Indonesia under Astra International. FIF offers easy application processes for new motorcycle credit, especially for Honda motorcycles, with fast, secure procedures and simple requirements such as ID card, family card, and salary slip. Applications can be made offline through dealers or FIF branch offices, as well as online. FIF also provides various flexible tenor options and down payment amounts according to consumers’ financial capabilities. Additionally, FIF continuously develops digital services and collaborates with dealers to enhance customer experience. New motorcycle financing is a major focus of FIF, contributing about 65% of total financing. FIF also strives to expand its service reach through automotive exhibitions and opening new branches. With competitive interest rates and an easy process, FIF helps the public own new motorcycles on credit in an affordable and trustworthy way. This study aims to provide a clear overview of the new motorcycle credit financing services at FIF.-